Steroids in neurooncology: actions, indications, side-effects - Roth, Patrick; Wick, Wolfgang; Weller, Michael (Current opinion in neurology, 2010)
Purpose of review - Glucocorticoids are frequently used in the treatment of patients with neurooncological disorders. This review addresses different clinical indications and provides information on beneficial and undesired effects exerted by these drugs. The most important cellular mechanisms of action of glucocorticoids under different conditions are highlighted. - Recent findings - Glucocorticoids have been used for the treatment of lymphoid neoplasms for decades. In addition to proapoptotic effects, recent studies have delineated the induction of autophagy in lymphoma cells as an important alternative mode of cell death. In contrast, glucocorticoids may reduce the sensitivity of tumor cells, including glioma cells, other than lymphoma cells to chemotherapeutic agents. Corticosteroids also provide transient relief from neurological symptoms caused by increased intracranial pressure and edema associated with primary and secondary brain tumors. However, treatment with glucocorticoids is also commonly associated with considerable side-effects including hyperglycemia, myopathy, osteoporosis, lymphopenia and others. - Summary - Although in clinical use for more than 40 years in the field of neurooncology, steroids remain a central and essential part in the treatment of brain tumor patients. Along with improved therapeutic options and prolonged life expectancy of many of these patients, careful administration is required and long-term side-effects must be considered.